Modified EVA foamed colloidal particles and preparation method thereof
By adding nanocomposite powder and polysiloxane to the EVA foam particles, forming a flexible and rigid structure inside and an antibacterial composite powder, the contradiction between flame retardancy and elasticity of the EVA foam particles is solved, and the problem of achieving the problem of the flame retardancy of the EVA foam particles is achieved. The combination of high flame retardancy and good mechanical properties has broadened its application in the field of foamed shoes.
Patent Information
- Application Number
- CN202411773978.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-05
AI Technical Summary
EVA foamed rubber particles themselves do not have flame retardancy. Commonly used flame retardant fillers will affect their physical properties while improving the flame retardant effect, especially in the field of foamed shoes, which lead to increased density and decreased rebound.
By adding composite polysiloxane containing nanocomposite powder during the preparation of EVA foam particles, combining nanomagnesium carbonate, nickel metal organic framework and nanosilicon dioxide coating, a core shell with soft inside and hard outside is formed. and the material performance is enhanced by using end-hydroxy polydimethylsiloxane, while the modified graphene/silver composite powder is introduced to improve the antibacterial effect.
It achieves the improvement of the elasticity and mechanical properties of EVA foamed products while ensuring the flame retardant effect, and enhances the flame retardant performance through the adsorption of nanocomposite powder and fixation of CO2 gas, broadening its application range in the field of foamed shoe materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of EVA foam particles, and particularly relates to modified EVA foam particles and a preparation method thereof. Background Art
[0002] EVA foam particles generally include EVA main material, filler, foaming agent, promoter and other raw materials. EVA is ethylene-vinyl acetate copolymer. The EVA foam commonly referred to in the foaming industry actually also includes blended materials such as PE, POE and EPDM. After chemical foaming or physical foaming, foaming materials with excellent performance can be prepared.
[0003] EVA foam material is light, soft and has good impact resistance, and is widely used in the field of shoe material manufacturing. Chemical foaming materials have large and uneven pores. In recent years, more shoe material manufacturers prefer to use supercritical foaming physical foaming to manufacture shoe materials. Supercritical foaming uses carbon dioxide gas or nitrogen as a foaming agent, which dissolves and diffuses into EVA and other foaming particles under high temperature and high pressure conditions. The gas is released during the rapid pressure release process to form a smaller and more uniform pore structure with better mechanical properties.
[0004] EVA foam particles themselves are not flame retardant. Like other foam materials, they need to be compounded with flame retardants during the preparation process to improve their flame retardant effect. Commonly used flame retardant fillers such as magnesium carbonate can not only improve the flame retardancy of foam materials, but also affect their physical properties, especially in the field of foamed shoe materials, which will increase the density of the product and reduce its resilience. Summary of the invention
[0005] The invention aims to provide a modified EVA foamed rubber particle and a preparation method thereof. In the preparation process of the modified EVA foamed rubber particle, a composite polysiloxane containing a nano-composite powder is added to ensure the flame retardant effect of the EVA foamed product while improving its resilience.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing modified EVA foam particles comprises the following steps: Step 1: Add a magnesium nitrate solution with a mass fraction of 20% into a reactor, dissolve sodium carbonate and sodium hydroxide with deionized water, add them into the reactor under stirring conditions of 800-1000r / min, and then react at 120-130°C for 4-6h, cool naturally, centrifuge and filter, wash the filter cake with deionized water for 3-5 times, and vacuum dry to obtain nano magnesium carbonate powder with a particle size of 220-280nm.
[0007] Step 2: Dissolve nickel nitrate hexahydrate in anhydrous methanol and transfer it to a reactor, then add nano magnesium carbonate powder to the reactor, stir at 800-1000 r / min for 5-10 min, ultrasonically disperse for 3-5 min, add a 2% by mass methanol solution of 2-aminoterephthalic acid to the reactor, stir at 25-30° C. for 2-3 h, then stand at 35° C. for 20-24 h, centrifuge and filter, wash the filter cake with anhydrous methanol for 3-5 times, and vacuum dry to obtain a nano core powder.
[0008] Step 3: Add the nano core powder, sodium silicate nonahydrate and deionized water into a reactor, stir for 5-10 minutes at 500-800 r / min, then add a 5% hydrochloric acid solution into the reactor, adjust the pH value to 8.5-9.5, stir and react for 1-1.5 hours at 35-40°C and 600-800 r / min, stand and age at 60°C for 25-30 minutes, centrifuge and filter, wash the filter cake with deionized water for 3-5 times, and vacuum dry to obtain a nano composite powder with a particle size of 300-350 nm.
[0009] Step 4: Add the terminal hydroxyl polydimethylsiloxane into a vacuum kneader, heat it to 140-145°C at a rate of 3-5°C / min, then add the nanocomposite powder into the vacuum kneader, heat it to 175-180°C and knead it at 50r / min for 100-120min, cool it naturally, and obtain a composite polysiloxane.
[0010] Step 5: Add EVA elastomer, TPEE polyester elastomer, EVA-g-MAH elastomer, composite polysiloxane, modified graphene / silver composite powder and silane coupling agent KH550 into an internal mixer in a mass ratio of 70-80:7-10:6-8:5-6:1.5-2:0.3-0.35, and mix them at 80-85°C and 40r / min for 3-5min, then heat to 120-125°C and mix for 2-3min, and finally transfer to a twin-screw extruder for extrusion, pelletize, and obtain modified EVA foam particles.
[0011] Furthermore, in step 1, the dosage ratio of magnesium nitrate solution, sodium carbonate, sodium hydroxide and deionized water is 15 mL: 1.67 g: 2.16 g: 15 mL.
[0012] Furthermore, in step 2, the usage ratio of nickel nitrate hexahydrate, anhydrous methanol, nano-magnesium carbonate and methanol solution of 2-aminoterephthalic acid is 2g:250-300mL:4g:300mL.
[0013] Furthermore, in step 3, the mass ratio of the nano core powder, sodium silicate nonahydrate and deionized water is 10:6-6.5:120-150.
[0014] Furthermore, in step 4, the mass ratio of the terminal hydroxyl polydimethylsiloxane to the nanocomposite powder is 5:2-3.
[0015] Further, the modified graphene / silver composite powder in step 5 is prepared by the following steps: Step a: adding graphene oxide and newly prepared silver ammonia solution into a reactor, stirring at 500-600 r / min for 2.5-3 h, then dropping a 10% glucose solution into the reactor, continuing to stir and react for 2-2.5 h after the dropping is complete, then adding 2-3 times the volume of deionized water of the reaction solution into the reactor, filtering, washing the filter cake with deionized water for 2-3 times, vacuum drying, and grinding to obtain a graphene / silver composite powder.
[0016] Step b: The graphene / silver composite powder is evenly dispersed with anhydrous ethanol and transferred to a reactor, and then methyl thioglycolate is added to the reactor, and the reaction is stirred for 8-9 hours under nitrogen protection and 300-500r / min. The filter cake is washed with anhydrous ethanol for 2-3 times, vacuum dried, and ground to obtain a modified graphene / silver composite powder.
[0017] Furthermore, in step a, the usage ratio of graphene oxide, silver ammonia solution and glucose solution is 1-1.2 g: 300 mL: 20 mL.
[0018] Furthermore, in step b, the usage ratio of graphene / silver composite powder, anhydrous ethanol and methyl thioglycolate is 1 g: 20-25 mL: 0.1-0.12 g.
[0019] Further, the preparation method of the silver ammonia solution is as follows: Add a 2% by mass silver nitrate aqueous solution to the reactor, then add 2% by mass ammonia water to the reactor until a white precipitate is generated, then adjust the pH value to 12 with a 50 g / L sodium hydroxide solution, and then continue to add 2% by mass ammonia water until the white precipitate is completely dissolved to obtain a silver ammonia solution.
[0020] Beneficial effects of the present invention: 1. Adding composite polysiloxane containing nano-composite powder during the preparation of the modified EVA foam particles of the present invention helps to simultaneously improve the resilience and flame retardant effect of the EVA foam products.
[0021] The nano-composite powder has nano-core powder particles as the core and nano-silicon dioxide coating as the shell. The matrix of the nano-core powder is nano-magnesium carbonate powder, and a nickel metal organic skeleton is generated in situ on the outside. The nano-silicon dioxide coating has a higher hardness, so that the nano-composite powder particles form a core-shell structure that is soft inside and hard outside. This structure helps to deflect the propagation of cracks and torsional cracks and disperse stress, thereby improving the mechanical properties of the modified EVA foam particles such as the rebound resilience.
[0022] The terminal hydroxyl polydimethylsiloxane can improve the viscoelasticity of EVA foam particles. During the kneading process at 175-180°C, the silanol groups on the surface of the nano-composite powder and the terminal hydroxyl groups of the terminal hydroxyl polydimethylsiloxane are cross-linked, and the formed Si-O-Si bonds can strengthen the material and further improve the mechanical properties of the material.
[0023] The nickel metal organic framework has a good adsorption capacity for gas. It adsorbs and fixes CO2 gas during the foaming process of EVA foam particles, releases CO2 gas when heated during the combustion process, causes the nano-composite powder particles to expand, and promotes the formation of an insulating carbon layer during combustion, thereby enhancing the flame retardant properties of the material.
[0024] 2. The modified graphene / silver composite powder improves the antibacterial effect through the synergistic effect of graphene and metallic silver. The thiol group in methyl thioglycolate reacts with metallic silver to form an ester group, which can improve the dispersibility of the modified graphene / silver composite powder, help improve the antibacterial effect of the modified EVA foam particle foaming product, and broaden its application range in the field of foamed shoe materials. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Embodiment 1: This embodiment provides a modified EVA foamed rubber particle, which is prepared by the following method: S1: 1500L of 20% magnesium nitrate solution was added into the reactor, 167kg of sodium carbonate and sodium hydroxide were dissolved with 1500L of deionized water, and then added into the reactor under stirring at 800r / min, and then reacted at 120°C for 4h, naturally cooled, centrifuged and filtered, the filter cake was centrifugally washed 3 times with deionized water, and vacuum dried to obtain nano magnesium carbonate powder with a particle size of 220-280nm.
[0027] S2: Dissolve 10kg of nickel nitrate hexahydrate in 1250L of anhydrous methanol and transfer to a reactor, then add 20kg of nano magnesium carbonate powder to the reactor, stir at 800r / min for 5min, ultrasonically disperse for 3min, add 1500L of 2% 2-aminoterephthalic acid methanol solution to the reactor, stir at 25°C for 2h, then stand at 35°C for 20h, centrifuge, wash the filter cake with anhydrous methanol for 3 times, and vacuum dry to obtain nano core powder. After the nano magnesium carbonate powder adsorbs nickel ions, it reacts with 2-aminoterephthalic acid as an organic ligand to generate a nickel metal organic skeleton in situ on the surface of the nano magnesium carbonate powder particles.
[0028] S3: 10 kg of nano core powder, 6 kg of sodium silicate nonahydrate and 120 L of deionized water were added to a reactor, stirred at 500 r / min for 5 min, and then a 5% by mass hydrochloric acid solution was added to the reactor, the pH value was adjusted to 8.5, and the reaction was stirred at 35°C and 600 r / min for 1 h. The mixture was allowed to stand at 60°C for 25 min, and filtered by centrifugation. The filter cake was washed three times by centrifugation with deionized water and dried in vacuo to obtain a nano composite powder with a particle size of 300-350 nm.
[0029] S4: Add 10 kg of terminal hydroxyl polydimethylsiloxane into a vacuum kneader, heat it to 140°C at a rate of 3°C / min, then add 4 kg of nano-composite powder into the vacuum kneader, heat it to 175°C and knead it at 50 r / min for 100 min, cool it naturally, and obtain composite polysiloxane.
[0030] S5: Add a 2% by mass silver nitrate aqueous solution into the reactor, then drop 2% by mass ammonia water into the reactor until a white precipitate is formed, then adjust the pH value to 12 with a 50 g / L sodium hydroxide solution, and then continue to drop 2% by mass ammonia water until the white precipitate is completely dissolved to obtain a silver ammonia solution.
[0031] 2 kg of graphene oxide and 600 L of freshly prepared silver ammonia solution were added to a reactor and stirred at 500 r / min for 2.5 h. Then, 40 L of 10% glucose solution was added dropwise to the reactor. After the addition was completed, the stirring reaction was continued for 2 h. Metallic silver was loaded on the surface of the graphene oxide. Deionized water with a volume of 2 times that of the reaction solution was added to the reactor, filtered, and the filter cake was washed twice with deionized water, vacuum dried, and ground to obtain a graphene / silver composite powder.
[0032] S6: 2 kg of graphene / silver composite powder was evenly dispersed with 40 L of anhydrous ethanol and transferred to a reactor, and then 0.2 kg of methyl thioglycolate was added to the reactor. The reaction was stirred for 8 hours under nitrogen protection and 300 r / min. The thiol group in the methyl thioglycolate coordinated with metallic silver. The mixture was filtered and the filter cake was washed twice with anhydrous ethanol, vacuum dried, and ground to obtain modified graphene / silver composite powder.
[0033] S7: 70 kg of EVA elastomer, 7 kg of TPEE polyester elastomer, 6 kg of EVA-g-MAH elastomer, 5 kg of composite polysiloxane, 1.5 kg of modified graphene / silver composite powder and 0.3 kg of silane coupling agent KH550 were added to an internal mixer, and the mixture was internally kneaded at 80 ° C and 40 r / min for 3 min, then heated to 120 ° C and internally kneaded for 2 min, and finally transferred to a twin-screw extruder for extrusion, pelletized, and modified EVA foam particles were obtained.
[0034] Embodiment 2: This embodiment provides a modified EVA foamed rubber particle, which is prepared by the following method: S1: 1500L of 20% magnesium nitrate solution was added into the reactor, 167kg of sodium carbonate and sodium hydroxide were dissolved with 1500L of deionized water, and then added into the reactor under stirring at 900r / min, and then reacted at 125°C for 5h, naturally cooled, centrifuged and filtered, the filter cake was centrifugally washed 4 times with deionized water, and vacuum dried to obtain nano magnesium carbonate powder with a particle size of 220-280nm.
[0035] S2: Dissolve 10 kg of nickel nitrate hexahydrate in 1350 L of anhydrous methanol and transfer the solution to a reactor. Add 20 kg of nano magnesium carbonate powder to the reactor, stir at 900 r / min for 8 min, and ultrasonically disperse for 4 min. Add 1500 L of 2% by mass 2-aminoterephthalic acid methanol solution to the reactor, stir at 28°C for 2.5 h, and then let stand at 35°C for 22 h. Centrifuge and wash the filter cake 4 times with anhydrous methanol. Dry under vacuum to obtain nano core powder.
[0036] S3: 10 kg of nano core powder, 6.2 kg of sodium silicate nonahydrate and 135 L of deionized water were added to a reactor, stirred at 650 r / min for 8 min, and then a 5% by mass hydrochloric acid solution was added to the reactor, the pH value was adjusted to 9, and the reaction was stirred at 38°C and 700 r / min for 1.2 h. The mixture was allowed to stand at 60°C for 28 min, and filtered by centrifugation. The filter cake was washed 4 times by centrifugation with deionized water and dried in vacuo to obtain a nano composite powder with a particle size of 300-350 nm.
[0037] S4: Add 10 kg of terminal hydroxyl polydimethylsiloxane into a vacuum kneader, heat it to 144°C at a rate of 4°C / min, then add 5 kg of nano-composite powder into the vacuum kneader, heat it to 178°C and knead it at 50 r / min for 110 min, cool it naturally, and obtain composite polysiloxane.
[0038] S5: Add a 2% by mass silver nitrate aqueous solution into the reactor, then drop 2% by mass ammonia water into the reactor until a white precipitate is formed, then adjust the pH value to 12 with a 50 g / L sodium hydroxide solution, and then continue to drop 2% by mass ammonia water until the white precipitate is completely dissolved to obtain a silver ammonia solution.
[0039] 2.2 kg of graphene oxide and 600 L of freshly prepared silver ammonia solution were added to the reactor and stirred at 550 r / min for 2.8 h. Then, 40 L of 10% glucose solution was added dropwise to the reactor. After the addition was completed, the stirring reaction was continued for 2.2 h. Then, deionized water twice the volume of the reaction solution was added to the reactor, filtered, and the filter cake was washed with deionized water for 2-3 times, vacuum dried, and ground to obtain graphene / silver composite powder.
[0040] S6: 2 kg of graphene / silver composite powder was evenly dispersed with 45 L of anhydrous ethanol and transferred to a reactor, and then 0.22 kg of methyl thioglycolate was added to the reactor. The reaction was stirred for 8.5 h under nitrogen protection and 400 r / min. The filter cake was washed twice with anhydrous ethanol, vacuum dried, and ground to obtain a modified graphene / silver composite powder.
[0041] S7: 75 kg of EVA elastomer, 8.5 kg of TPEE polyester elastomer, 7 kg of EVA-g-MAH elastomer, 5.5 kg of composite polysiloxane, 1.8 kg of modified graphene / silver composite powder and 0.32 kg of silane coupling agent KH550 were added to an internal mixer, and the mixture was internally kneaded at 82 ° C and 40 r / min for 4 min, then heated to 122 ° C and internally kneaded for 2.5 min, and finally transferred to a twin-screw extruder for extrusion, pelletized, and modified EVA foam particles were obtained.
[0042] Embodiment 3: This embodiment provides a modified EVA foamed rubber particle, which is prepared by the following method: S1: 1500L of 20% magnesium nitrate solution was added into the reactor, 167kg of sodium carbonate and sodium hydroxide were dissolved with 1500L of deionized water, and then added into the reactor under the stirring condition of 1000r / min, and then reacted at 130°C for 6h, naturally cooled, centrifuged and filtered, the filter cake was centrifugally washed with deionized water for 5 times, and vacuum dried to obtain nano magnesium carbonate powder with a particle size of 220-280nm.
[0043] S2: Dissolve 10 kg of nickel nitrate hexahydrate in 1500 L of anhydrous methanol and transfer it to a reactor. Add 20 kg of nano magnesium carbonate powder to the reactor, stir at 1000 r / min for 10 min, ultrasonically disperse for 5 min, add 1500 L of 2% by mass 2-aminoterephthalic acid methanol solution to the reactor, stir at 30°C for 3 h, then stand at 35°C for 24 h, centrifuge and wash the filter cake with anhydrous methanol for 5 times, and vacuum dry to obtain nano core powder.
[0044] S3: 10 kg of nano core powder, 6.5 kg of sodium silicate nonahydrate and 150 L of deionized water were added to a reactor, stirred at 800 r / min for 10 min, and then a 5% by mass hydrochloric acid solution was added to the reactor, the pH value was adjusted to 9.5, and the reaction was stirred at 40°C and 800 r / min for 1.5 h. The mixture was allowed to stand at 60°C for 30 min, and filtered by centrifugation. The filter cake was washed 5 times by centrifugation with deionized water, and dried in vacuo to obtain a nano composite powder with a particle size of 300-350 nm.
[0045] S4: Add 10 kg of terminal hydroxyl polydimethylsiloxane into a vacuum kneader, heat it to 145°C at a rate of 5°C / min, then add 6 kg of nano-composite powder into the vacuum kneader, heat it to 180°C and knead it at 50 r / min for 120 min, cool it naturally, and obtain composite polysiloxane.
[0046] S5: Add a 2% by mass silver nitrate aqueous solution into the reactor, then drop 2% by mass ammonia water into the reactor until a white precipitate is formed, then adjust the pH value to 12 with a 50 g / L sodium hydroxide solution, and then continue to drop 2% by mass ammonia water until the white precipitate is completely dissolved to obtain a silver ammonia solution.
[0047] 2.4 kg of graphene oxide and 600 L of freshly prepared silver ammonia solution were added to the reactor and stirred at 600 r / min for 3 h. Then, 40 L of 10% glucose solution was added dropwise to the reactor. After the addition was completed, the stirring reaction was continued for 2.5 h. Then, 3 times the volume of deionized water of the reaction solution was added to the reactor, filtered, and the filter cake was washed 3 times with deionized water, vacuum dried, and ground to obtain graphene / silver composite powder.
[0048] S6: 2 kg of graphene / silver composite powder was evenly dispersed with 50 L of anhydrous ethanol and transferred to a reactor, and then 0.24 kg of methyl thioglycolate was added to the reactor. The reaction was stirred for 9 hours under nitrogen protection and 500 r / min. The filter cake was washed three times with anhydrous ethanol, vacuum dried, and ground to obtain modified graphene / silver composite powder.
[0049] S7: 80 kg of EVA elastomer, 10 kg of TPEE polyester elastomer, 8 kg of EVA-g-MAH elastomer, 6 kg of composite polysiloxane, 2 kg of modified graphene / silver composite powder and 0.35 kg of silane coupling agent KH550 were added to an internal mixer, and the mixture was internally kneaded at 85 ° C and 40 r / min for 5 min, then heated to 125 ° C and internally kneaded for 3 min, and finally transferred to a twin-screw extruder for extrusion, pelletized, and modified EVA foam particles were obtained.
[0050] Comparative Example 1: Based on Example 3, in step S7, the composite polysiloxane is replaced with the nano-magnesium carbonate powder in step S1 of the same mass, and the other steps remain unchanged to prepare modified EVA particles.
[0051] Comparative Example 2: Based on Example 3, without going through step S2, the nano-magnesium carbonate powder in step S1 is directly substituted for the nano-core powder and the operation is performed according to step S3 to prepare nano-composite powder, and the remaining steps remain unchanged to prepare modified EVA particles.
[0052] Comparative Example 3: Based on Example 3, the nano-composite powder in step S3 does not undergo the kneading operation in step S4, and the terminal hydroxyl polydimethylsiloxane and the nano-composite powder are directly mixed in a mass ratio of 10:6 in step S4 and applied to the subsequent steps, that is, according to step S7, 6 kg of composite polysiloxane is replaced by 3.75 kg of terminal hydroxyl polydimethylsiloxane and 2.25 kg of nano-composite powder, and the remaining steps remain unchanged to prepare modified EVA granules.
[0053] Comparative Example 4: Based on Example 3, 2 kg of graphene oxide was directly processed according to the method in step S6 to prepare modified graphene oxide without going through step S5, and then the modified graphene / silver composite powder in step S7 was replaced, and the remaining steps remained unchanged to prepare modified EVA granules.
[0054] Comparative Example 5: Based on Example 3, without going through step S6, step S7 directly replaces the modified graphene / silver composite powder with the same mass of graphene / silver composite powder in step S5, and the other steps remain unchanged to prepare modified EVA particles.
[0055] The model of the EVA elastomer in the embodiments and comparative examples is Japan Mitsui EVA 550; the model of the TPEE polyester elastomer is the American DuPont 3078; the model of the EVA-g-MAH elastomer is the American Exxon VA 1202; the terminal hydroxyl polydimethylsiloxane is purchased from Shenzhen Jipeng Silicon Fluoride Materials Co., Ltd.; and the graphene oxide is purchased from Jiangxi Shuobang New Materials Technology Co., Ltd.
[0056] The performance tests were conducted on Examples 1 to 3 and Comparative Examples 1 to 5. The modified EVA particles were prepared into EVA foam materials by supercritical foaming. The supercritical foaming gas was CO2, the pressure was 26 MPa, and the temperature was 150°C. Different samples were prepared according to the corresponding test methods: According to GB / T 6343-2009 "Determination of apparent density of foam plastics and rubber", the density of different samples was tested by drainage method; According to GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)", refer to method B: use right-angled specimens, cut, and test the tear strength of different specimens; The compression set rate of different samples was tested according to Method A of GB / T 6669-2008 "Determination of compression set of flexible foam polymeric materials"; The resilience of different samples was tested in accordance with GB / T 6670-2008 "Determination of rebound properties of soft foam polymer materials by falling ball method"; the antibacterial rate of different samples was tested in accordance with QB / T 2881-2013 "Technical conditions for antibacterial properties of footwear and footwear components", and the test strains included Staphylococcus aureus (ATCC 6538) and Escherichia coli (ATCC 11229); According to GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method Part 2: Room Temperature Test", the limiting oxygen index of different samples is tested. The larger the value, the better the flame retardant effect.
[0057] The results are shown in Table 1: Table 1 Performance test results of different EVA foam material samples
[0058] As can be seen from Table 1, the samples in Examples 1 to 3 have lower compression permanent deformation and higher resilience. The composite polysiloxane has a viscoelastic segment, which can improve the resilience of the EVA foam particles foamed product. The performance in Comparative Example 3 is lower than that in Example 3 because the terminal hydroxyl polydimethylsiloxane and the nanocomposite powder in the example are kneaded at 175-180°C. At this temperature, the silanol on the surface of the nanocomposite powder and the terminal hydroxyl of the terminal hydroxyl polydimethylsiloxane are cross-linked, and the formed Si-O-Si bond can enhance the EVA foam particles.
[0059] Comparative Example 1 shows that directly adding nano magnesium carbonate powder will lead to a decrease in the mechanical properties of the sample, while in Comparative Example 2, the tear strength increases, and the other mechanical properties are relatively low, because the reinforcing effect of nano magnesium carbonate is poorer than that of nano silicon dioxide. In the embodiment, the nano composite powder has nano core powder particles as the core, the nano silicon dioxide coating layer as the shell, the matrix of the nano core powder is nano magnesium carbonate powder, and a nickel metal organic skeleton is generated in situ on the outside. The hardness of the nano silicon dioxide coating layer is higher, so that the nano composite powder particles form a core-shell structure with soft inside and hard outside. This structure helps to propagate deflection cracks and twist cracks, disperse stress, and thus improve the mechanical properties of the modified EVA foaming particles foaming product.
[0060] The limiting oxygen index in Comparative Example 2 is lower, which may be because the nano-composite powder particles contain a nickel metal organic skeleton, which has a good adsorption capacity for gas, adsorbs and fixes CO2 gas during the foaming process of the EVA foam particles, and releases CO2 gas when heated during the combustion process, causing the nano-composite powder particles to expand, thereby enhancing the flame retardant properties of the material.
[0061] Comparative Example 4 shows that the modified graphene / silver composite powder can improve the antibacterial effect of the modified EVA foam particle foaming product, and the graphene and metallic silver synergistically play an antibacterial role; the antibacterial performance in Comparative Example 5 is slightly poor because it is not modified by methyl thioglycolate, resulting in poor dispersibility of the graphene / silver composite powder.
[0062] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing modified EVA foam particles, characterized in that: The steps include: Step 1: Add nano core powder, sodium silicate nine hydrate and deionized water into a reaction kettle in a mass ratio of 10:6-6.5:120-150, stir at 500-800 r / min for 5-10 min, add 5wt% hydrochloric acid solution to adjust the pH value to 8.5-9.5, stir at 35-40°C and 600-800 r / min for 1-1.5h, stand at 60°C for aging for 25-30min, centrifuge and filter, wash the filter cake with deionized water for 3-5 times, and vacuum dry to obtain a nano composite powder with a particle size of 300-350nm; Step 2: Add the terminal hydroxyl polydimethylsiloxane into a vacuum kneader, heat it to 140-145°C at a rate of 3-5°C / min, then add the nano-composite powder and heat it to 175-180°C, knead it at a speed of 50r / min for 100-120min, and cool it naturally to obtain a composite polysiloxane; the mass ratio of the terminal hydroxyl polydimethylsiloxane to the nano-composite powder is 5:2-3; Step 3: Add EVA elastomer, TPEE polyester elastomer, EVA-g-MAH elastomer, composite polysiloxane, modified graphene / silver composite powder and silane coupling agent KH550 into an internal mixer in a mass ratio of 70-80:7-10:6-8:5-6:1.5-2:0.3-0.35, and mix them at 80-85°C and 40r / min for 3-5min, then heat to 120-125°C and mix for 2-3min, and finally transfer to a twin-screw extruder for extrusion, pelletize, and obtain modified EVA foam particles.
2. The method for preparing a modified EVA foamed particles according to claim 1, characterized in that: The nano core powder is prepared by the following steps: Nickel nitrate hexahydrate is dissolved in anhydrous methanol and transferred to a reactor, and then nano magnesium carbonate powder is added, stirred at 800-1000 r / min for 5-10 min, ultrasonically dispersed for 3-5 min, 2 wt% methanol solution of 2-aminoterephthalic acid is added to the reactor, stirred at 25-30° C. for 2-3 h, allowed to stand at 35° C. for 20-24 h, centrifuged and filtered, the filter cake is centrifuged and washed 3-5 times with anhydrous methanol, and vacuum dried to obtain nano core powder.
3. A method for preparing modified EVA foam particles according to claim 2, characterized in that: The usage ratio of the nickel nitrate hexahydrate, anhydrous methanol, nano-magnesium carbonate and the methanol solution of 2-aminoterephthalic acid is 2g:250-300mL:4g:300mL.
4. A method for preparing modified EVA foam particles according to claim 2, characterized in that: The nano magnesium carbonate is prepared by the following steps: A 20wt% magnesium nitrate solution is added into a reaction kettle, and then sodium carbonate and sodium hydroxide are dissolved in deionized water and added into the reaction kettle under stirring conditions of 800-1000r / min, reacted at 120-130°C for 4-6h, naturally cooled, centrifuged and filtered, the filter cake is centrifugally washed with deionized water for 3-5 times, and vacuum dried to obtain nano magnesium carbonate powder with a particle size of 220-280nm.
5. A method for preparing modified EVA foam particles according to claim 4, characterized in that: The dosage ratio of the magnesium nitrate solution, sodium carbonate, sodium hydroxide and deionized water is 15 mL: 1.67 g: 2.16 g: 15 mL.
6. The method for preparing modified EVA foam particles according to claim 1, characterized in that: The modified graphene / silver composite powder is prepared by the following steps: The graphene / silver composite powder is evenly dispersed with anhydrous ethanol and transferred to a reaction kettle, and then methyl thioglycolate is added, and the reaction is stirred for 8-9 hours under nitrogen protection and 300-500r / min. The filter cake is washed with anhydrous ethanol 2-3 times, vacuum dried, and ground to obtain a modified graphene / silver composite powder.
7. The method for preparing modified EVA foam particles according to claim 6, characterized in that: The usage ratio of the graphene / silver composite powder, anhydrous ethanol and methyl thioglycolate is 1 g: 20-25 mL: 0.1-0.12 g.
8. The method for preparing modified EVA foam particles according to claim 6, characterized in that: The graphene / silver composite powder is prepared by the following steps: Add graphene oxide and the newly prepared silver ammonia solution into a reactor, stir at 500-600 r / min for 2.5-3 h, then drop 10 wt % glucose solution into the reactor, continue stirring and reacting for 2-2.5 h after the dropwise addition is complete, then add 2-3 times the volume of deionized water of the reaction solution into the reactor, filter with suction, wash the filter cake with deionized water for 2-3 times, vacuum dry, and grind to obtain graphene / silver composite powder; The usage ratio of the graphene oxide, the silver ammonia solution and the glucose solution is 1-1.2 g: 300 mL: 20 mL.
9. The method for preparing modified EVA foam particles according to claim 8, characterized in that: The silver ammonia solution is prepared by the following method: A 2wt% aqueous silver nitrate solution was added to the reactor, and then 2wt% aqueous ammonia was added dropwise to form a white precipitate. The pH value was adjusted to 12 with a 50g / L sodium hydroxide solution, and 2wt% aqueous ammonia was continued to be added dropwise until the white precipitate was completely dissolved to obtain a silver ammonia solution.
10. A modified EVA foamed rubber particle, characterized in that: The modified EVA foam particles are prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
High-resilience aging-resistant EVA foamed material and preparation method thereof
CN106117766A
Transparent foam sole formulation and method of using formulation to make sole
CN107501713A
Method for preparing lightweight high-elastic wear-resistant rubber and plastic material by using regenerated EVA (ethylene-vinyl acetate)
CN113308044A
Modified EVA, preparation method thereof and wide-temperature-range high-performance EVA composite foaming material
CN113845716A
Graphene modified rubber and plastic foamed colloidal particles and preparation method thereof
CN116554535A